Remediation of 2,4,6-Trichlorophenol from Aqueous Solution by Raw and Chemical Modified Date Palm Stone Biomass: Kinetics and Isotherms Studies - Nadavala Siva Kumar; Mohammad Asif; Anesh Manjaly Poulose; Ebrahim H. Al-Ghurabi; Shaddad S. Alhamedi; Janardhan Reddy Koduru (BioResources, 2024)
Raw and citric acid chemically treated date palm stone agro-waste biomass (RDSB and CA-MDSB) powders were used to remove an important class of emerging industrial pollutants, i.e., 2,4,6-trichlorophenol (2,4,6-TCP) from aqueous solutions towards sustainable waste utilization to develop cost-effective technology for treating wastewater. The biomass characterization was performed by using different analytical techniques such as CHN elemental analysis, particle size, BET, FTIR, and SEM-EDX, TGA analysis. The FTIR spectral analysis revealed that the main chemical groups (N–C, O=C, H-O, H-C, and O–C) were involved in trapping 2,4,6-TCP. The highest adsorption was achieved with a contact time of 150 and 120 min, an initial concentration of 50-200 mg/L, and a biosorbent dosage ranging from 0.1 to 1.0 g/L RDSB and CA-MDSB, respectively. The experimental kinetic data of the adsorption process for both adsorbents (RDSB and CA-MDSB) fitted very well with the pseudo-second-order kinetic model and Langmuir equilibrium data. The 2,4,6-TCP maximum monolayer adsorption capacities were 53.7, and 123.8 mg/g for RDSB and CA-MDSB, respectively. The present research confirms that the date palm stone biomass could be used as an effective and low-cost biosorbent for the remediation of 2,4,6-TCP from an aqueous environment.